2005
DOI: 10.1158/1541-7786.mcr-05-0106
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Induces Cyclooxygenase-2 and Vascular Endothelial Growth Factor Receptor-2 in Association with Tumor-Associated Invasion and Angiogenesis in Gastric Cancer

Abstract: Blockade of angiogenesis is a promising strategy to suppress tumor growth, invasion, and metastasis. Vascular endothelial growth factor (VEGF), which binds to tyrosine kinase receptors [VEGF receptors (VEGFR) 1 and 2], is the mediator of angiogenesis and mitogen for endothelial cells. Cyclooxygenase-2 (COX-2) plays an important role in the promoting action of nicotine on gastric cancer growth. However, the action of nicotine and the relationship between COX-2 and VEGF/VEGFR system in tumorigenesis remain undef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 47 publications
2
67
0
Order By: Relevance
“…In addition to hypoxia-responsive elements, the promoters of VEGF share many consensus sites for Sp1/Sp3, AP-2, Egr-1, and signal transducers and activators of transcription 3 (48). Previous studies have reported that nicotine stimulates VEGF expression in cancer cells (6,14,49), but the underlying mechanisms remain largely unknown. In this study, we showed that nicotine significantly stimulated VEGF production, which can be partially inhibited (f46.8%) by disrupting HIF-1a expression using siRNA strategy (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hypoxia-responsive elements, the promoters of VEGF share many consensus sites for Sp1/Sp3, AP-2, Egr-1, and signal transducers and activators of transcription 3 (48). Previous studies have reported that nicotine stimulates VEGF expression in cancer cells (6,14,49), but the underlying mechanisms remain largely unknown. In this study, we showed that nicotine significantly stimulated VEGF production, which can be partially inhibited (f46.8%) by disrupting HIF-1a expression using siRNA strategy (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Although in neurons, the ␣7-nAChRs participate in neurotransmission which is blocked by ␣-bungarotoxin (␣-BTX) and methyllycaconitine (MLA) (16,17), it is unlikely that these receptors perform such a function in nonexcitable cells. Chronic in vivo nicotine treatment suppresses the immune and inflammatory responses (18 -20), causing T cell anergy (21) and decreased leukocyte migration; however, acute exposure to nicotine increases intracellular calcium [Ca 2ϩ ] i and cell migration in several cell types (18,14,22,23). In vivo, nicotine regulates T cell function by direct interaction with T cells and indirectly through neuroimmune interactions (18,24).…”
Section: T He Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%
“…Nicotine exerts its biologic function mainly through nicotinic acetylcholine receptors (nAChR), b-adrenoreceptors (b-AR), and/or EGF receptors (EGFR) in the motor endplates of muscle and the nervous system (11)(12)(13). The nAChR is also expressed in various cancer cells (14,15). Recent studies have demonstrated that nicotine regulates multiple signaling proteins, especially phospho-specific Akt (pAkt) in lung, oral, and breast cancer cells (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%